2023
DOI: 10.1021/jacsau.3c00365
|View full text |Cite
|
Sign up to set email alerts
|

DNA Nanoribbon-Assisted Intracellular Biosynthesis of Fluorescent Gold Nanoclusters for Cancer Cell Imaging

Xiangyuan Ouyang,
Nan Jia,
Jing Luo
et al.

Abstract: Metal nanoclusters (NCs) have emerged as a promising class of fluorescent probes for cellular imaging due to their high resistance to photobleaching and low toxicity. Nevertheless, their widespread use in clinical diagnosis is limited by their unstable intracellular fluorescence. In this study, we develop an intracellularly biosynthesized fluorescent probe, DNA nanoribbon-gold NCs (DNR/AuNCs), for longterm cellular tracking. Our results show that DNR/AuNCs exhibit a 4-fold enhancement of intracellular fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Different to the above tactics, Ouyang et al proposed long-term cellular tracking by intracellularly biosynthesized Au NCs [74]. In their study, the DNA nanoribbon could promote the formation of Au NCs in tumor cells and showed a 4-fold enhancement in comparison to free Au NCs.…”
Section: Cancer Cellsmentioning
confidence: 99%
“…Different to the above tactics, Ouyang et al proposed long-term cellular tracking by intracellularly biosynthesized Au NCs [74]. In their study, the DNA nanoribbon could promote the formation of Au NCs in tumor cells and showed a 4-fold enhancement in comparison to free Au NCs.…”
Section: Cancer Cellsmentioning
confidence: 99%
“…To ensure controlled drug release, stimulus-responsive polymeric micelle drug delivery systems have been investigated. These systems offer enhanced stability in normal tissues and rapid drug release in tumor microenvironments. Polymeric prodrug micelles containing chemotherapeutic drugs linked with cleavable chemical bonds prevent drug leakage during circulation and respond to stimuli at the tumor site, triggering drug release. Notably, GSH is crucial in maintaining intracellular redox balance and is associated with various diseases. Hence, selective detection and quantification of GSH hold valuable information for disease prognosis . Several GSH-responsive drug release systems have been rationally designed for cancer treatment due to the significant difference between intracellular and extracellular GSH concentrations, and tumor cells contain a higher concentration of GSH, which is 4–7 times that of normal cells …”
Section: Introductionmentioning
confidence: 99%
“… 13 24 Notably, GSH is crucial in maintaining intracellular redox balance and is associated with various diseases. 25 29 Hence, selective detection and quantification of GSH hold valuable information for disease prognosis. 30 Several GSH-responsive drug release systems have been rationally designed for cancer treatment due to the significant difference between intracellular and extracellular GSH concentrations, and tumor cells contain a higher concentration of GSH, which is 4–7 times that of normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a suitable scaffold is necessary for stabilizing AuNCs, such as polymer, thiols, amines, DNA, proteins, and peptides. 5,12–19 The rational selection of the scaffold can regulate sizes, optical properties and stability to obtain a variety of AuNCs. 20,21 Proteins and peptides are composed of amino acid monomers connected by amide bonds.…”
Section: Introductionmentioning
confidence: 99%